Greeting Strategies Employed by Javanese People - Mochamad Rizqi Adhi Pratama (Faculty of Economics, Law, and Humanities, 2018)
Javanese has been becoming fruitful sources of data especially in Pragmatic field. However, nobody has concerned the greeting strategies they employed. This study is aimed at investigating the greeting strategies employed by Javanese people in Mangunsari village, Semarang, Indonesia. The notion of greeting strategies has not got quite considerable attention by Pragmatic researcher since there are only few studies concerning them. As utterances and verbal communication should be interpreted based on the socio-cultural background, Javanese cannot be separated from the concept of Javanese culture like friendliness. As a result, the verbal communication they uttered might have more meaning than the said. Therefore, this study also attempts to trace the implicature they intent. This paper examines how greeting strategies are manifested and conveyed within the major framework of the Javanese culture. This study is about socio-cultural pragmatics in which utterances are discussed in relation to their situation and cultural background which support them. The data are in the form of dialogue between Javanese which does not show any different social status among the interlocutors. The data of this research were collected by recording and note taking (for the parts in which recording is not possible). The data are aimed at generating the strategies used by Javanese (in Mangunsari village, Semarang, Indonesia) to maintain harmony among the members. Finally, the data are examined from general theory of implicature and the Javanese culture concept (friendliness). This study provides important findings showing that Javanese tend to greet others by employing a particular way which differ from common ways of greeting. They employed the utterances to imply their friendliness as a harmony and relation maintenance and to avoid the sense of arrogant and individualistic.Keywords: greeting strategies, friendliness, implicature, harmony